2014
DOI: 10.1039/c3dt52112e
|View full text |Cite
|
Sign up to set email alerts
|

Mineralization of DNA into nanoparticles of hydroxyapatite

Abstract: Encapsulation of DNA into hydroxyapatite (HAp) has been investigated using a rational approach that involves computer simulation and experimental techniques. The temporal evolution of the radial distribution functions derived from atomistic molecular dynamics simulations of Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 42 publications
(73 citation statements)
references
References 33 publications
4
68
0
Order By: Relevance
“…The biomineralization process of DNA has been not only observed experimentally but also described at the molecular level using atomistic computer simulations. [4,7] Here we explore the synergies for life development based on bioinorganic interactions between DNA and HAp and the role of HAp in biochemical reactions. We consider cell death as a trigger of biomineralization process and the processes of reintroduction of the biomineralized DNA in the life cycle, drawing conclusions on how DNA could pass on the mass extinction events.…”
Section: Hydroxyolitementioning
confidence: 99%
See 1 more Smart Citation
“…The biomineralization process of DNA has been not only observed experimentally but also described at the molecular level using atomistic computer simulations. [4,7] Here we explore the synergies for life development based on bioinorganic interactions between DNA and HAp and the role of HAp in biochemical reactions. We consider cell death as a trigger of biomineralization process and the processes of reintroduction of the biomineralized DNA in the life cycle, drawing conclusions on how DNA could pass on the mass extinction events.…”
Section: Hydroxyolitementioning
confidence: 99%
“…[1][2][3] Biomineralization of desoxirribonucleic acid (DNA) has recently been studied at atomic level [4][5][6][7] revealing that DNA acts as a template for hydroxyapatite (HAp) crystallization ( Figure 1). As a consequence, HAp adsorbs or encapsulates DNA and thus protects the biomolecule from external attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, polyP was proposed to play an important role in cartilage mineralization and bone Despite fifteen years ago Okazaki et al 34 proposed that DNA inhibits HAp growth, more recent studies proved that the formation of HAp can be regulated by DNA, which acts as a template in the process of "biomineralization". [35][36][37][38] Thus, the role of DNA as template to promote mineral formation and the own biomineralization mechanism has been recently examined at the atomic level. [35][36][37][38] Results showed that calcium phosphate clusters are formed surrounding the polyP backbone of DNA, which acts as a very large nucleus for the growing of the HAp.…”
Section: O Pmentioning
confidence: 99%
“…The model for the biomineral was constructed considering the following experimental observations: (i) carbonate and Mg 2+ substitution in HAp, extensively observed in living organisms, may increase its solubility; [6][7][8] and (ii) the solubility also increases with decreasing crystallinity. [12] Initially, a HAp nanoparticle of composition similar to that found in previous experimental studies [6] was constructed using Ca…”
Section: Construction Of the Molecular Modelmentioning
confidence: 99%
“…[3] In recent years the formation mechanism of HAp biominerals on ds-DNA soft templates has been investigated and characterized. [5][6][7][8] Nevertheless, the molecular mechanism that drives the particle dissolution and DNA demineralization remains widely unknown and controversial. [9][10][11] In this work we use a four-step approach based on atomistic molecular dynamics (MD) simulations to clarify the dissolution mechanism of HOli in acid environments, mimicking the physiological pH variations of the intracellular fluid encountered inside the cell cytosol and nucleus.…”
Section: Introductionmentioning
confidence: 99%